Analogy and Exemplary Reasoning in Legal Discourse. - Kaptein, Hendrik (Amsterdam University Press, 2017)
This book brings together contributions from leading figures in legal studies on analogy and related forms of reasoning in the law. Analogical reasoning--which relies on the concept of two different things being in some way like each other--is hugely important not just in the practice of law, but it is nonetheless strongly contested. This volume raises key questions like: What is the logical, argumentative, rhetorical, or just heuristic force of analogy in law? Is analogy really different from extensive interpretation, reasoning by precedent and appeal to paradigm?